Asuhan Keperawatan Pemenuhan Kebutuhan Cairan Pada Pasien Dengue Haemorrhagic Fever Di Rumah Sakit Tk II Putri Hijau Medan - Paulina Taurista Pakpahan; Purwaningsih Purwaningsih; Erita Gustina (Jurnal Kesehatan dan Fisioterapi, 2022)
Background: Dengue Haemorrhagic Fever (DHF) is a disease that often worries people and this disease can cause death. According to WHO data (2014), Dengue Haemorrhagic Fever was first reported in Southeast Asia in 1954, namely in the Philippines, then spread to various countries. The purpose of this study is to be able to overcome the fulfillment of fluid needs in DHF patients. Dengue Haemorrhagic Fever is an infectious disease causedby the dengue virus and belongs to the Arbovirus (arthropod-borne virus) group which is transmitted through the Aedes aegypti and Aedes albopictus mosquito vectors and spreads very quickly. This research method is descriptive in the case study design covering the stages os assessment, diagnosis, intervention, implementation and evaluation. The results of the study on 2 DHF patients obtained that the problem of fluid fulfillment was resolved by full monitoring of intake and output. It is hoped that the results of this study can be used as material for further research for researchers who will conduct research on fluid volume deficiency in Dengue Haemorrhagic Fever patients. Based on the research conducted, both respondents experiencedfluid fulfillment from those who initially experienced a shortage to become fulfilled.Keyword: Dengue Haemorrhagic Fever, Fulfillment of Fluid Needs